Social media marketing : A strategic approach - a Barker, Melissa S. (Mason, Ohio, South-Western, Cengage Learning, 2013)
Social Media Marketing: A Strategic Approach promises to be the seminal textbook in the field with its distinctive conceptual foundation and practical approach to developing successful social media marketing plans. A proven eight-step social media planning model provides students with a cumulative learning experience, showing them how to construct social media strategies that achieve desired marketing goals.
Includes Index.